Teknik Pengenalan Bacaan dan Gerakan Shalat pada Anak - Gita Ajeng Kinanti; Mavianti Mavianti (Departement of Mathematics Education, 2023)
Prayer is the second pillar of Islam. a human obligation. Prayer is part of a religious practice that is used as a means of worshiping God. Prayer is considered valid and perfect if the prayer is carried out in compliance with the requirements and pillars and things that are sunnah and regardless of things that cancel it. The conditions for prayer are something that must be fulfilled before we pray . The conditions for prayer are conditions that must be fulfilled, namely: Islam, understanding and tamziz or baligh. sacred from menstruation and childbirth and has heard the invitation of Islamic da'wah. Prayer for young children, especially those aged 5 to 6 years is not yet an obligation, because children are not yet mature, but parents are obliged to introduce prayer as a mandatory worship and other forms of worship from an early age. The purpose of this research is to improve the technique of introducing reading and prayer movement in children at Tadika Al-Fikh Orchard, Pendamar Indah 2, Selangor, Malaysia. The method in this study was a qualitative descriptive method. The results of this study indicate that the children's ability to pray has increased significantly, because most children are happy and interested in praying directly in Tadika and at home and encourage them to get used to praying with tu'maninah and humility, and to be able to recite the prayer readings properly and correctly.